The Free Abelian Group in R: The Frab Package - Hankin, Robin (arXiv, 2023)
In this short article I introduce the frab package which provides an alternative interpretation of named vectors in the R programming language; it is available on CRAN. The underlying mathematical object is the free Abelian group.
Keywords: 4904 Pure Mathematics; 49 Mathematical Sciences